Insoluble Additives for Enhancing a Blood-Like Liquid Flow in Micro-Channels - Abdulbari, Hayder A.; Fiona Ling, Wang Ming; Wafaa, Kamil Mahmood (Elsevier Ltd, 2017)
This study introduces an approach for flow enhancement in the bloodstream using insoluble additives as non-degradable drag reducing agents that can replace the polymeric soluble additives. An open micro-channel liquid flow system with three different channel sizes was assembled and used to test the drag reduction performances of the solutions investigated. Three different nanopowders (with five different addition concentrations) were investigated and used to form solutions of artificial blood with blood-like rheological properties. The experimental results showed that the optimum drag reduction performance was achieved using bismuth III oxides (65%) for a 200 ppm concentration solution flowing through a 100 µm channel, while titanium IV oxides and fumed silica achieved 57 and 55% drag reduction for a 200 ppm concentration solution flowing in a 50 μm channel, respectively.